A Reliable Solution for Sparsity Problem in Collaborative Filtering Using Demographic Approach - Goud, Kaira Nithin (International Journal of Computer Sciences and Engineering, 2019)
Now a day’s online resources are increasing very rapidly like amazon and flipchart, eBay etc. The main role of recommendation systems is to provide recommendations based upon the ratings given by the users.it suffers from the sparsity to reduce that we are going to introduce a reliable solution that motives to perform better results using a demographic approach. Each prediction consorts with a reliability measure. Reliability is a measure of how liable a prediction is. So each recommendation for a user is associated with a pair of values those are Prediction and reliability. Quality of reliability is also discussed. Experimental results show that our proposed reliable solution using demographic approach has increased the overall recommendation and reduced the sparsity.